Influence of Social Media on Post-Purchase Dissonance : An Empirical Study - Shyam Prasad, S.; Y. K., Amruta (Indian Journal of Marketing, 2023)
Purpose : Post-purchase dissonance refers to a customer’s dissatisfaction after buying a product or service. This study focused on the role of social media in influencing customer dissonance. The growing online purchases and product returns due to dissatisfaction have increased the importance of post-purchase dissonance. This fact induced us to undertake this study. Methodology : The data for this study were collected online via a questionnaire using Google Forms. We prepared the questionnaire after carefully reviewing the extant literature. Eight items were adopted from the scale developed by Sweeney et al. (2000). Using R software, multiple regression models were used to analyze the data and test the hypotheses. Finally, a structural equation model was developed to establish the model fit. Findings : In this study, we found that online purchases by themselves alone did not result in postpurchase dissonance. However, social media has been found to have a significant moderating role in precipitating dissonance. Practical Implications : The findings of this study are both important and straightforward. Firms should closely monitor social media. Social media can easily sway the cognitive balance that the customers may have reached before making a purchase. With the increased social media usage to check for products before purchases (Mason et al., 2021), it has become all the more important for firms to keep a close watch on social media. Originality : The study’s originality lies in the fact that the study considered the role of social media, particularly in online purchases..